Birth and tectono-sedimentary evolution of the Tertiary Piedmont Basin (NW Italy) - Ghibaudo, Guido; Massari, Francesco; Chiambretti, Igor; d'Atri, Anna; Fornaciari, Eliana (Journal of Mediterranean Earth Sciences, 2019)
The Tertiary Piedmont Basin (TPB), located at the Alps-Apennines junction, is a polyhistory basin representing a key area for the comprehension of the complex evolution of Alps-Apennines junction. An updated litho-and biostratigraphy of the southern part of the basin fill is presented, together with a reconstruction of the stratal architecture, main sedimentologic features, tectonic-driven sequential organization, and main unconformities. Selected units having more appeal for the sedimentology and stratal organization, and/or role played in the geologic evolution of the study area, are described in more detail, mainly with reference to measured sections. The geological evolution is viewed in both regional and supra-regional contexts. In Priabonian to earliest Rupelian times an episutural composite basin, not yet differentiated from the North-Apenninic domain, was generated in the eastern TPB (the Borbera-Grue area) located on the northward prosecution of an inferred major crustal discontinuity lining the eastern margin of the Corsica-Sardinia block; in this paleogeographic domain deposition occurred in rapidly subsiding depocentres controlled by strike-slip tectonics, and characterized by geometry and dimensions variable through time, and highly unstable source areas. An important step of this early history is the deposition of the Savignone Conglomerate interpreted as large-scale Gilbert-type delta complex prograding into a pull-apart trough subject to extremely high subsidence rate. In the middle Rupelian crustal stretching concurrent with post-orogenic exhumation of the Mesoalpine prism led to the generation of a horst and graben topography and expansion of coarse-grained sedimentation to the whole TPB. Extensional strain probably occurred in the rear of the nascent Apennines, in concomitance with the onset of rollback of the downgoing Adriatic slab, which is thought to have been fostered since ca. 32 Ma by the propagation of a slab tear from beneath the Alps into the Ligurian area; the extensional process is kinematically compatible with the coeval backarc rifting generated in the Liguro-Provençal area. The graben infilling conglomerates laid down during this stage show diachronous deposition with westward younging trend and facies associations changing westwards from deep-water turbiditic to continental. In the late middle Rupelian the extensional regime turned into a left-lateral strike-slip regime with probably pure sinistral motion. First activation of the left-stepping major lineaments represented by the Villalvernia-Varzi Line to the NE and the Stura fault system to the SW is thought to have caused the conversion of the TPB into a left-stepover strike-slip basin located between the opposite Alpine and Apenninic subductions. This evolution is thought to reflect the onset of NW-ward translation of the Adriatic Indenter. Since the latest middle Rupelian a dramatic drowning and accelerated subsidence in a regime of inferred right-lateral transtension affected the basin, setting up the deposition of basinwide slope hemipelagites of the Rocchetta Fm encasing bodies of coarse-grained resedimented deposits, particularly important in the Langhe and Borbera-Grue depocentres. Although already delineated during the deposition of the Molare Fm, the separation the TPB and N-Apennine Epiligurian domains was definitive with the onset of deposition of the Rocchetta Fm. Indeed, the paleocurrent pattern, geometry, and sandstone composition of the turbidite bodies are compatible with the rise at that time of a morphologic-tectonic boundary most probably corresponding in position to the VV Line. In the Late Chattian-Aquitanian the transtension turned, with a certain westward younging diachroneity, into a main left-lateral transpressional episode, attributed to the change in the direction of motion of the Adriatic Indenter with respect to Europe from NW-ward to WNW-ward, resulting in conditions of oblique convergence and increased collisional coupling. The sequence of tectonic and stratigraphic events affecting the TPB in the Rupelian to Aquitanian time span occurred with a definite E-W diachroneity expressed by a westward younging trend, thought to reflect the concurrent role of Apenninic subduction and translation of the Adriatic Indenter in controlling the geologic evolution of the basin in this time span. Siliceous deposits, occurring at several levels in the Aquitanian to lower Langhian interval of the TPB succession, represent marker horizons on regional scale and are interpreted as slope or base-of-slope hemipelagites originally rich in biosiliceous component due to events of increased organic productivity, favouring basinwide blooms of siliceous phytoplankton. The late Chattian- Aquitanian transpressional tectonics enhanced the paleogeographic differentiation between the uplifting Alto Monferrato High, and adjacent sub-basins of the Langhe and Borbera-Grue areas. In the early Burdigalian a marine transgression occurred with gaps of various amplitude on the deformed substrate of the Alto Monferrato High, where it took place with a characteristic backstepping pattern linked to cyclic relative sea level fluctuations, with formation of incised shorefaces during episodes of relative stillstand. The Alto Monferrato High was then the site of deposition of lower Burdigalian ramp carbonates and outer shelf marls, whereas in the flanking sub-basins continued a hemipelagic deposition punctuated by the emplacement of several bodies of resedimented, commonly coarse deposits of mixed carbonate and terrigenous composition, locally as infills of structural troughs or submarine valleys. A strike-slip regime continued in the TPB mainly as a result of the onset of counterclockwise rotation of the TPB; it is particularly reflected in the stratigraphic architecture of the Uzzone Valley area (Langhe Sub-basin), controlled by a NE-SW growth fault system. The rotation, beginning in the Burdigalian, occurred with an angle close to the that of the Sardinia-Corsica Block ( 50°) and higher than that estimated for the rotation of the Adria indenter (20-25°). This indicates a partly independent behavior and supports the contention that in this stage the Sardinia-Corsica block and the Liguria area, including the TPB, behaved as a unique microplate interposed between the European and Adria plates, SE of the Ligurian Sea collapse. A major tectonic reorganization occurred in the TPB since the middle Burdigalian, with dramatic acceleration of subsidence coinciding with the deposition of slope deposits of the Pratolungo Fm, marking on the Alto Monferrato High an extremely fast platform drowning episode, and the laterally equivalent Serole Fm of the Langhe area, both grading upwards to a basinwide turbidite system, the upper Burdigalian Cortemilia Fm, showing an eastward transition from lobe deposits to a basin plain facies association. This turnover probably occurred in concomitance with the onset of emplacement of the “Front of the Alpine Axial Sector” (AXF) a deep-seated, arcuate, north-verging thrust accommodating the displacement of buried elements of the axial Alpine belt. This tectonic event is thought to mark the onset of northward thrust propagation toward the Padan foredeep and is interpreted to reflect the beginning of a process of underplating. The subsequent history until recent times was one of continuing outward migration of the Padan thrust fronts toward the Padan foredeep accompanied by pronounced uplift of the TPB margins, leading to progressive reduction of extent and northward shift of basin depocentres and concomitant development of the Alessandria and Savignano basins since the Langhian. The westward tilt and uplift of the Borbera- Grue sector in the Langhian is testified by basin inversion and a major hinged margin erosional unconformity of eastward increasing importance at the base of the Cessole Formation. This unit developed as a complex sediment wedge prograded westwards into the Langhe Sub-basin and later onlapped by the turbidites of the Cassinasco Fm; this in turn shows a spectacular wedging out eastwards with onlap onto the Alto Monferrato structural high. Deposition on this high in the Serravallian was characterized by the migration of a field of sandwaves consisting of coarse hybrid arenites; the depositional setting was typified by an interaction between ephemeral storm-driven flows, and more continuous tractive flows producing sandwave trains. Sandwave migration probably occurred in a seaway between the Alps and the neo-Apennines, with formation of sandwave field controlled by strait-related tidal current amplification and occurring in concomitance with the input of coarse fan-delta detritus from the denudation of uplifted south-eastern areas. Tectonic-driven forced regression in late Serravallian is recorded by a significant coarsening trend of the fan-delta input accompanied by local development of a shelf incised valley on the Alto Monferrato High. Continuing N-S contraction was concomitant with an important episode of E-W extension in the Tortonian, leading to an incipient rifting followed by a rapid platform drowning recorded by basinwide deposition of the hemipelagic Sant’Agata Fossili Marl. The rifting, interpreted as far-reaching effect of the coeval E-W back-arc extension which affected the Tyrrhenian Basin since 10-9 Ma, was accompanied by persisting gravity instability and important mass wasting episodes, the most important of which is the failure of the western margin of the Alto Monferrato High, wich generated the Rocca Grimalda Chaotic Complex including giant slide blocks (olistoliths) of Serravalle Sandstone and Cessole Fm. Progressive confinement of the depositional environment at the Tortonian- Messinian transition and during the early Messinian is linked with the well-known paleogeography established in the Mediterranean since the late Tortonian. A characteristic rhythm, generally interpreted as precession-driven, consists of alternating bioturbated marls with benthic faunas indicating bottom oxygenation and blackish laminites devoid of any benthic faunal element indicating bottom water anoxia. Two important erosional unconformities mark the base of the intra-Messinian Valle Versa chaotic complex and respectivey the base of the upper Messinian fan-delta/lagoonal Cassano Spinola Conglomerate, showing affinity with the well-known “Strati a Congerie” of the “Lago Mare”. The latter unit shows an overall trend coarsening upwards, reflecting the tectonic-driven progradation of the fan-delta system into a lagoonal-lacustrine body of water.